2020
DOI: 10.1089/chi.2019.0059
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Childhood Obesity Risk: A Systematic Review

Abstract: Background: Childhood overweight and obesity are recognized as predictors of the risk of obesity in adulthood. The aim of this systematic literature review was to determine the association between dietary pattern and obesity risk among children. Methods: Articles were selected from databases (Cochrane Library, Lilacs, Eric, Livivo, and PubMed/Medline), without limitations regarding language or date. Database-specific search terms included the key words ''obesity,'' ''diet,'' ''dietary pattern,'' ''childhood,''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
146
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 71 publications
11
146
0
15
Order By: Relevance
“…Empirical dietary patterns usually differ across studies. For that reason, we tried to label the found dietary patterns with the same nomenclature than other studies [ 14 ]. However, we also considered the way the Chilean population eats the foods included in the patterns to reflect their habitual meals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical dietary patterns usually differ across studies. For that reason, we tried to label the found dietary patterns with the same nomenclature than other studies [ 14 ]. However, we also considered the way the Chilean population eats the foods included in the patterns to reflect their habitual meals.…”
Section: Discussionmentioning
confidence: 99%
“…There is now evidence that dietary patterns, rather than individual nutrients or foods, contribute to disease trajectories because empirical dietary patterns evaluate the food consumption under a multidimensional approach that takes into account the effects of the overall diet [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, how the consumption of different foods is integrated within specific dietary patterns, particularly in LAC countries where there is great cultural and dietary diversity, is unclear [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, a recent systematic review has proven the role of dietary patterns in the prediction of obesity at early ages. 50 According to their results, those children and adolescents who adhered to obesogenic food patterns (ie, including sugary drinks, processed foods, fast food, candies, and refined grains) were more likely to develop obesity. Interestingly, they concluded that additional confounders such as physical activity should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Food preferences and dietary patterns are developed in early childhood and can influence later habits [ 3 , 4 ]. Nutrition in early childhood influences both short- and long-term health including growth and development, risk of overweight and obesity, and related chronic disease [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%